Implementasi Kebijakan Tata Cara Pendaftaran Izin Usaha Mikro Dan Kecil Di Kecamatan Alang-Alang Lebar Kota Palembang - Saputra, Ardodi Julian; Sandy, Amiruddin; Sakir, Icuk Muhammad (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
This research aims to analyze the implementation of policies on registration procedures for micro and small enterprises (UMK) in Alang-Alang Lebar District, Palembang City. The MSE registration policy is an important step in supporting the growth of the informal sector and ensuring the sustainability of small businesses in the region. This research uses a qualitative descriptive approach, with data collection methods through in-depth interviews with business actors and sub-district officials, as well as field observations. The research results show that the implementation of this policy has gone quite well, although there are still several obstacles, such as a lack of socialization and public understanding of registration procedures, as well as limited human resources at the sub-district level. Factors that influence implementation effectiveness include apparatus capacity, awareness of business actors, as well as technological and infrastructure support. Recommendations are given to increase outreach, strengthen apparatus capacity, and utilize technology to speed up the MSE registration process in Alang-Alang Lebar District. With these improvements, it is hoped that the policy can be more effective in encouraging local economic growth and improving community welfare.